2020
DOI: 10.1038/s41467-019-13798-8
|View full text |Cite
|
Sign up to set email alerts
|

Forest management in southern China generates short term extensive carbon sequestration

Abstract: Land use policies have turned southern China into one of the most intensively managed forest regions in the world, with actions maximizing forest cover on soils with marginal agricultural potential while concurrently increasing livelihoods and mitigating climate change. Based on satellite observations, here we show that diverse land use changes in southern China have increased standing aboveground carbon stocks by 0.11 ± 0.05 Pg C y −1 during 2002-2017. Most of this regional carbon sink was contributed by newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
185
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(224 citation statements)
references
References 64 publications
10
185
0
1
Order By: Relevance
“…The other part of increased PWA came from SWA, which is related to many reasons, such as the fluctuated rainfall, temperature due to climate change and other aspects [77,78]. Moreover, similar to the PWA increased during 2000~2017, our study found that the greenness and carbon cycle also increased in this region, this is identical to the recent studies, in which the SWC is greening and carbon stocks is raising [79,80].…”
Section: Responses Of Seasonal Indicators To Droughtssupporting
confidence: 88%
“…The other part of increased PWA came from SWA, which is related to many reasons, such as the fluctuated rainfall, temperature due to climate change and other aspects [77,78]. Moreover, similar to the PWA increased during 2000~2017, our study found that the greenness and carbon cycle also increased in this region, this is identical to the recent studies, in which the SWC is greening and carbon stocks is raising [79,80].…”
Section: Responses Of Seasonal Indicators To Droughtssupporting
confidence: 88%
“…6; Φ RG and Φ TL are the sets of renewable generators and interchange tie-lines, respectively. Constraint (9) shows the spinning reserve requirement, where P CG i;max is the installed capacity of the i th coal-fired generator, and R(t) is the reserve requirement at time slot t. Constraint (10) shows the lower and upper limits for coal-fired generators' power, where P CG i;min is the minimal power when the i th coal-fired generator is online. Constraints (11) and (12) show the relationships between U i (t), Y i (t), and Z i (t).…”
Section: Methodsmentioning
confidence: 99%
“…An efficient and stable remote sensing data processing method could integrate a volume of images, which would be meaningful in monitoring the urbanization process and analyzing the co-evolution of multi-cities [41][42][43]. Several methods have been developed in recent years to take advantages of time series of remotely sensed images for LULC detection, including the Landsat-based detection of Trends in Disturbance and Recover (LandTrendr) [44,45], the vegetation change tracker (VCT) [46], and the Continuous Change Detection and Classification (CCDC) algorithm [17,33,[47][48][49][50]. These methods are designed to analyze the changes of ground objects through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are designed to analyze the changes of ground objects through different mechanisms. LandTrendr detects abrupt change by the segmentation method and, between the abrupt changes, a slope is fitted for each segment to capture the gradual changes, and this approach has been used for insect infestation detection and forest change detection [44,47,51,52]. The VCT normalizes each Landsat image into a forest probability index and uses a thresholding method to detect forest disturbance.…”
Section: Introductionmentioning
confidence: 99%